HOW DID THE MYTH OF THE GLASS WORLD BECOME TRUE? - Turg'unboyeve Ziyoda Shuhratjon qizi; Mirkomilov Baxtiyor Mirkomilovich (European Science Publishing, 2024)
This article provides information about the reasons for the discovery, development and popularization of television, which has become an integral part of our daily life.
Keywords: Alisher Navoi, A. S. Popov, B. L. Rozing, B. Povlovich N. G. Piskunov, I. Olimjonava, Y. Stolyarova, window to the world, USA, Great Britain, Petersburg, Moscow, Tashkent, Samarkand, Fergana.